CHINA’S NEAR-ARCTIC STATE AMBITIONS AND OVERLAP WITH PACIFIC MARITIME DEFENCE: BLIND SPOTS FOR THE U.S. AND INDIA - Tripathi, Ishita; Bindra, S.S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
China’s self-designation as a “near-Arctic state” in its 2018 Arctic Policy represents a critical expansion of its strategic footprint beyond the Indo-Pacific, signalling an intent to integrate Arctic access routes and resources into the framework of the Belt and Road Initiative (BRI). While global attention often focuses on the South China Sea and Indian Ocean as theatres of naval rivalry, the overlooked linkages between China’s Arctic ambitions and its Pacific maritime defence strategy are reshaping the broader security architecture. This paper examines how Beijing’s pursuit of the Polar Silk Road, cooperation with Russia over the Northern Sea Route (NSR), and investments in dual-use infrastructure align with its blue-water naval expansion in the Pacific. It argues that U.S. and Indian strategic postures exhibit a significant blind spot by treating the Arctic and Pacific theatres in isolation, thereby underestimating China’s integrative approach to maritime defence. In its methodology, the study utilises a mixed framework: (i) it observes the advancement of official policy documents, white papers, and strategy reports between 2017 and 2025; (ii) it investigates the maritime traffic and infrastructure along the Bering Strait and NSR; and (iii) it compares the U.S. and India's Arctic and Indo-Pacific strategies. The results of this study illustrate how China strengthens its naval posture in the Pacific by utilising its "near-Arctic" location for establishing energy, logistics, and underwater surveillance capabilities. The approaches of the United States and India remain separated, with the U.S. prioritising Arctic competitiveness with Russia and India concentrating on scientific diplomacy, resulting in serious shortcomings in marine domain awareness and chokepoint management. This study contributes to ongoing scholarly debates by highlighting the ways in which China's Arctic-Pacific nexus defies contemporary maritime defence paradigms and by recommending actionable strategies for policymakers in both New Delhi and Washington. By highlighting how China's Arctic-Pacific connection contradicts current marine defence paradigms and suggesting policy recalibrations for Washington and New Delhi, this article adds to the body of knowledge.